Penguatan Konsumsi Rumah Tangga dan Edukasi Mini Buklet Kepada Civitas Akademika Unesa Terdampak Covid-19 - Dhiah Fitrayati; Muhammad Abdul Ghofur; Albrian Fiky Prakoso; Mohamad Arief Rafsanjani; Eka Hendi Andriansyah (Universitas Lancang Kuning, 2021)
The impact of the Covid-19 pandemic on the economic sector is quite heavy. Based on data from the Ministry of Manpower as of April 7, 2020, it was recorded that 39,977 companies in the formal sector chose to lay off and lay off their workers. A total of 1,010,579 workers were affected. This condition results in a decline in people's purchasing power. In fact, one of the prevention efforts so that it is not easily infected with Covid-19 is to maintain the body's immune system through healthy food and lifestyle. In an effort to suppress the spread of Covid-19, the PKM Team provided Covid-19 prevention education through mini booklets and provided assistance in the form of commodities to increase body immunity for the Unesa academic community in the East Java region, especially Surabaya. The Unesa academic community who received Covid-19 prevention education through mini booklets and provided assistance in the form of immune-boosting commodities as many as 20 people consisting of students and educational staff.